2020
DOI: 10.3390/agronomy10081099
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Nested-MultiLocus Sequence Typing Approach for A Highly Sensitive and Specific Identification of Xylella fastidiosa Subspecies Directly from Plant Samples

Abstract: Identification of sequence types (ST) of Xylella fastidiosa based on direct MultiLocus Sequence Typing (MLST) of plant DNA samples is partly efficient. In order to improve the sensitivity of X. fastidiosa identification, we developed a direct nested-MLST assay on plant extracted DNA. This method was performed based on a largely used scheme targeting seven housekeeping gene (HKG) loci (cysG, gltT, holC, leuA, malF, nuoL, petC). Samples analyzed included 49 plant species and two insect species (Philaenus spumari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Methods of detection for X. fastidiosa include microscopy, immunological assays and molecular methods [12], none of which require culturing. Also, identification of X. fastidiosa to the subspecies level by quantitative PCR (qPCR) and to the strain level using multilocus sequence typing (MLST) can be performed using DNA directly extracted from plants [13,14]. However, to reconstruct transmission chains, whole-genome sequencing is necessary to identify a sufficient number of SNPs for phylogenetic analysis.…”
mentioning
confidence: 99%
“…Methods of detection for X. fastidiosa include microscopy, immunological assays and molecular methods [12], none of which require culturing. Also, identification of X. fastidiosa to the subspecies level by quantitative PCR (qPCR) and to the strain level using multilocus sequence typing (MLST) can be performed using DNA directly extracted from plants [13,14]. However, to reconstruct transmission chains, whole-genome sequencing is necessary to identify a sufficient number of SNPs for phylogenetic analysis.…”
mentioning
confidence: 99%
“…The sensitivity of the primer pair was evaluated in different plant DNA backgrounds calibrated at an initial concentration of 5 × 10 5 copies.µL −1 . The fact that there are no differences between hosts in the sensitivity of the technique may be due to the use of BSA, which in other studies has been shown to compensate for polymerase inhibitors, and thus favor PCR efficiency [28]. In the same way, the gene could be amplified in naturally-infected samples from various hosts, where the lack of amplification was mainly related to a low concentration of bacterial cells (i.e., it was associated with high threshold values of Harper's qPCR assay) [29].…”
Section: Discussionmentioning
confidence: 95%
“…These samples showed a Ct > 30 for Harper's qPCR test, which was over the detection limit of the ND116-pRIV5-F1 and ND117-pRIV5-R1 primer pair. Indeed, for those samples, it was necessary to perform the Nested-MLST analysis [28] to assign the Xf isolate infecting the sample at the subspecies and ST level. Table 1.…”
Section: Pcr-based Plasmid Typing Of Xylella Fastidiosa Strains and N...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Majorca, both subspecies multiplex and fastidiosa have been detected in P. spumarius (Cesbron et al, 2020;Moralejo et al, 2020), and under experimental conditions, their role as a vector has been confirmed for bacterial transmission between almond and almond, vine to vine, and vine to almond tree (Cesbron et al, 2020;Moralejo et al, 2020). Other insects considered potential vectors in Majorca are N. campestris and N. lineatus (Olmo et al, 2021).…”
Section: Insect Vectors Of Xylella Fastidiosa On Prunus Spp Around the Worldmentioning
confidence: 87%